Impact of On-Job Training on Performance of Telecommunication Industry - Khan, Nadir; ., Muhammad Ibrahim; ., Muhammad Khalil Shahid (Journal of Social and Development Sciences, 2012)
This research is about On-Job training and Performance of organization. It discusses the importance of training and its output, which is very necessary for individual performance and over all organizational performance. In this research study, various variables, which are the outcome of Training, have been taken into account. Further, more the relationship of all those variables with the over all organizational performance has been studied. A structural model has been developed according to the results and relationship of these variables. The research will add a significant figure to the performance of organization and will raise the importance and value of training in organizations. The results are applicable to all type of organizations and will help managers to make their firms more productive and stable.